2011
DOI: 10.1681/asn.2010040339
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Nonphosphorylated Carboxylated Matrix Gla Protein Predicts Survival in ESRD

Abstract: The mechanisms for vascular calcification and its associated cardiovascular mortality in patients with ESRD are not completely understood. Dialysis patients exhibit profound vitamin K deficiency, which may impair carboxylation of the calcification inhibitor matrix gla protein (MGP). Here, we tested whether distinct circulating inactive vitamin K-dependent proteins associate with all-cause or cardiovascular mortality. We observed higher levels of both desphospho-uncarboxylated MGP (dp-ucMGP) and desphospho-carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
188
7
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 210 publications
(211 citation statements)
references
References 34 publications
12
188
7
4
Order By: Relevance
“…Five studies [10][11][12][13]24 reported on the association between mortality and dp-ucMGP in patients with aortic stenosis, 12 chronic 10 or end-stage kidney disease, 24 chronic heart failure, 11 or overt vascular disease. 13 The associations between all-cause mortality and dp-ucMGP were positive, 10-13 except in patients with advanced renal dysfunction, in whom this association was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies [10][11][12][13]24 reported on the association between mortality and dp-ucMGP in patients with aortic stenosis, 12 chronic 10 or end-stage kidney disease, 24 chronic heart failure, 11 or overt vascular disease. 13 The associations between all-cause mortality and dp-ucMGP were positive, 10-13 except in patients with advanced renal dysfunction, in whom this association was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Lower levels of calcification inhibitors (fetuin-A, matrix GLA protein) were observed in vascular diseases, whereas OPG levels were elevated (44,45,46). So far, myostatin has not been implicated in mineral homeostasis crucial for the pathophysiology of vascular calcification.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in CKD and T2D patients serum ucMGP levels correlated inversely with CAC and peripheral arterial calcification scores 42,43 although plasma dp-ucMGP levels were positively correlated with calcification scores 43 and mortality 44 , but not with risk of CHD or stroke after 11.5 years 45 . Similarly, a large study of asymptomatic subjects found that higher dp-ucMGP was associated with higher mortality, including cardiovascular mortality, but lower coronary event incidence 46 , possibly reflecting the protective effect of coronary calcification by stabilising plaque. Likewise, lower levels of dp-cMGP were associated with a higher calcification score and all-cause and CV mortality in CKD 47 .…”
Section: Calcificationmentioning
confidence: 93%